2011
DOI: 10.1007/s11325-011-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologist's knowledge and attitudes about obstructive sleep apnea: a survey study

Abstract: The study shows that anesthesiologists lack adequate knowledge about OSA. The total correct score ratio was 62%; when they managed an OSA patient, the positive attitude score is mostly below 50%. They have low confidence about OSA patients. It is necessary to develop special training programs on OSA regularly for anesthesiologists after graduation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…Moreover, less than 50% were aware of the fact that untreated OSA is a major cause of car accidents (27), indicating a lack of knowledge of the socioeconomic impact of this condition. Italian anaesthetists participating in this survey performed slightly better (66%) when compared to anaesthetists included in the recent Wang et al (19) (62%) and worse than physicians enrolled in other studies, with average of knowledge responses of 76% in selected physicians for the Schotland and Jeffe (15) 78% for family practitioners (16), 79% for Cardiologists and internists (17), and 67% for paediatricians (18). These results might reflect greater familiarity with OSA due to different post-graduate training programs and an increasing number of publications regarding OSA in different specialties other than anaesthesia (28)(29)(30).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, less than 50% were aware of the fact that untreated OSA is a major cause of car accidents (27), indicating a lack of knowledge of the socioeconomic impact of this condition. Italian anaesthetists participating in this survey performed slightly better (66%) when compared to anaesthetists included in the recent Wang et al (19) (62%) and worse than physicians enrolled in other studies, with average of knowledge responses of 76% in selected physicians for the Schotland and Jeffe (15) 78% for family practitioners (16), 79% for Cardiologists and internists (17), and 67% for paediatricians (18). These results might reflect greater familiarity with OSA due to different post-graduate training programs and an increasing number of publications regarding OSA in different specialties other than anaesthesia (28)(29)(30).…”
Section: Discussionmentioning
confidence: 68%
“…In various studies using OSAKA questionnaire in adults, the knowledge score in cardiologists, anesthetists and primary care physicians was 76, 62 and 60%, respectively [17][18][19]. Similarly knowledge score (regarding pediatric OSA by using OSAKA kids) of Chinese pediatricians and ENT specialists was 64.1 ± 19.1% [20].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Moreover, these studies focused on specific areas of medicine including cardiology and pulmonology. It is likely that increased awareness of OSA might have generally led to an increase in referral rates for OSA evaluation in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have not reported any significant knowledge and attitudinal changes, nor has there been improvement in referrals for OSA evaluation among physicians. 23,28,29 Indeed, much has been gained since OSA was first described in the literature. While understanding the physiological mechanisms of this condition has important clinical implications, the education and attitudes of providers should be considered in any intervention that aims to increase awareness of OSA.…”
Section: Discussionmentioning
confidence: 99%